Penerapan Model Pembelajaran Self Learning dalam Meningkatkan Prestasi Belajar Siswa - Kristian Yohanis Nokas; Andreas Ande (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
This study aims to analyze the implementation of the self-learning model in improving students' academic achievement in sociology. This research employed Classroom Action Research (CAR), conducted in two cycles, consisting of planning, action, observation, and reflection stages. The subjects were 36 students of class XI IPS2 at SMA Negeri 1 SoE. Data were collected through observation, tests, and documentation and analyzed using descriptive quantitative methods. The results showed that before implementing the self-learning model, the level of learning mastery was only 22.22%. After the first cycle, it increased to 41.67% but had not yet met the classical mastery criteria. In the second cycle, there was a significant improvement, reaching 94.44%, indicating that most students met the required standard. This improvement demonstrates that the self-learning model enhances students’ independence, participation, and understanding of the material. Therefore, the self-learning model is proven effective in improving students' academic achievement in sociology.